Practices and Attitudes That Enhance Music Engagement of Adult Cochlear Implant Users - Gfeller, Kate; Mallalieu, Ruth MacMullen; Mansouri, Aleksander; McCormick, Gaelen; O’Connell, Renee Blue; Spinowitz, Jake; Gellinek Turner, Bettina (Frontiers in Neuroscience, 2019)
Background: Cochlear implants (CIs) are auditory prostheses designed to support spoken communication in persons with severe to profound hearing loss. Many postlingually deaf adult CI users achieve good speech recognition in quiet; unfortunately, CI technology conveys a degraded representation of pitch and timbre, essential components of music. Not surprisingly, most CI users achieve significantly poorer perception and enjoyment of music compared with normal hearing listeners. Anecdotal evidence indicates that this impacts music engagement, particularly singing and playing instruments requiring ongoing tuning to external pitches or producing intervallic ratios. Interestingly, a small cohort of adult CI users has shown remarkable success in recovering or developing musical skills, but their success is poorly understood. Greater understanding of their efforts and attitudes may suggest potential rehabilitative approaches for other CI users. Purpose: This article documents personal characteristics and experiences that contribute to high level musicianship in CI users. Research questions include: 1) What forms of practice/experience have most contributed to (re)establishing satisfying music making? 2) What situations or musical tasks are most frustrating or challenging? 3) What attitudes, motivational factors, or forms of support help CI users persist in working toward improved music engagement? Methods: The overall approach is patient-engaged research methodology, which encourages active involvement of patients in the preparatory, execution, and translational phases of research. Patient input in research planning has facilitated higher rates of enrollment and retention, relevant translational applications of research, and has been applauded on an ethical basis. Our study involves a unique collaboration of six CI users and a researcher with 30 years of research experience regarding music and CIs. Using qualitative methods, the CI recipients conveyed their experiences and attitudes regarding music and CIs through open-ended narratives. These narratives were analyzed using an integrative approach of inductive and deductive coding methods. The codes that emerged through inductive methods were then organized within the Dynamic Problem Solving Model for Management of Complex Listening Environments. Outcomes: Themes include the importance of pre-CI music instruction, extensive practice and immersion in music listening and playing, persistence and self-efficacy, and problem solving skills that optimize music engagement.